Interactive Digital Art Exhibitions: Enhancing Public Engagement Through Technology in Fine Arts - Ngr. Putu Raka Novandra Asta; Rohmat Sahirin; Mariam Khan; Nguyen Minh Tu (Yayasan Adra Karima Hubbi, 2024)
Background. Interactive digital art exhibitions have emerged as a significant trend in the intersection of technology and fine arts. These exhibitions leverage digital tools and technologies to enhance public engagement, offering immersive experiences that traditional art displays often lack. With the rise of digital technologies, there is a growing interest in understanding how interactive elements influence the way audiences engage with art and how such exhibitions can make art more accessible to a wider audience. Purpose. This study aims to investigate the impact of interactive digital art exhibitions on public engagement, focusing on how technology can be utilized to create more immersive and participatory experiences for art viewers. Method. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with visitors of interactive digital art exhibitions. Data were collected from three art galleries hosting such exhibitions, with a sample of 200 participants. The study analyzed engagement levels, visitor feedback, and the role of technology in enhancing the art experience. Results. Findings indicate that interactive digital art exhibitions significantly increase visitor engagement, with 85% of participants reporting a deeper connection with the artwork. Technology, particularly interactive displays and virtual reality, was identified as a key factor in improving the audience’s overall experience. Conclusion. Interactive digital art exhibitions offer a novel approach to engaging the public in fine arts, making art more dynamic and accessible. The integration of technology enhances visitor interaction and creates more memorable and impactful experiences.